CONSTRUÇÃO SOCIAL DO RISCO. TECNOLOGIA E VULNERABILIDADE SOCIAL. - SOUZA, Emanuel P. de (2008)
The hegemony of the principles that define the rational use of the method and the application of scientific knowledge within the production process involve the contours of industrial society. Criticism of science and scientific theories and concepts of ownership of science by new actors through the subjectivation of these products of science define the emergence of a scenario where conflicts are to involve the definition of the risks involved in the expansion of technology on the world. This research is the analysis of a case study regarding the dispute concerning the judicial area adjacent to the equipment of the transmission system of high-voltage electrical energy into in a peripheral area of the city of Sao Luis do Maranhão. It shows the elements that guide the various ways in which those involved defining the risks present in that area. It as a type of study that shows different modes of ownership and representation spaces in the city. Therefore present the analysis of a kind of social conflict that characterizes our time and that starts to be strongly visible in the state of Maranhao.